Asperosaponin VI suppresses ferroptosis in chondrocytes and ameliorates osteoarthritis by modulating the Nrf2/GPX4/HO-1 signaling pathway - Zhang, Zhimeng; Yuan, Daotong; Jin, Ximin; Chang, Wenjie; Zhang, Yongkui; Xie, Wenpeng (Frontiers in Pharmacology, 2025)
BackgroundAsperosaponin VI (AVI) is a naturally occurring monosaccharide derived from Dipsacus asperoides renowned for its anti-inflammatory and bone-protective properties.ObjectiveTo elucidate the specific mechanism through which AVI affects chondrocytes in osteoarthritis (OA).MethodsFor the in vitro experiments, primary chondrocytes were to elucidate the molecular mechanisms underlying the action of AVI.For the in vivo experiments, rat OA models were established using a modified Hulth method. The severity of knee osteoarthritis was evaluated 8 weeks post-surgery. Micro-CT imaging, hematoxylin-eosin staining, and Safranin O-fast green staining were used to assess degeneration in rat knee joints. Immunohistochemistry techniques were conducted to measure the levels of collagen II, MMP13, Nrf2, GPX4, ACSL4, and HO-1 within cartilage tissues. ELISA assays were performed to measure those of TNF-α, IL -6, and PGE2 in serum samples.ResultsAVI alleviated chondrocyte apoptosis and extracellular matrix degradation in rat OA induced by IL-1β. It attenuated the levels of TNF-α, IL-6, and PGE2 while reducing those of Fe2+ and malondialdehyde (MDA). AVI upregulated the expression of Nrf2, HO-1, and GPX4 while downregulating that of ACSL4. Mechanistic studies revealed that ML385-induced inhibition of the Nrf2 signaling pathway reversed the increase in GPX4 and ACSL4 expression and increased Fe2+ and MDA levels; treatment with erastin, a ferroptosis inducer, produced comparable results. In vivo experiments demonstrated that AVI improved the bone volume/tissue volume and trabecular separation values in OA rats; reversed the Osteoarthritis Research Society International score; upregulated Nrf2, HO-1, and GPX4 expression; downregulated ACSL4 and MMP13 expression, and decreased the serum levels of TNF-α, IL-6, and PGE2.ConclusionOur findings suggest that AVI is a promising therapeutic agent for OA. It exerted its protective effect by regulating the Nrf2/GPX4/HO-1 signaling axis to inhibit cartilage cell ferroptosis and improve osteoarthritis.